El ocaso de un siglo: representaciones de Emilia Pardo Bazán en el diario El Pueblo (1899) - Blanca Cerdá Aznar (Cahiers de Civilisation Espagnole Contemporaine)
Emilia Pardo Bazán's trip to Valencia was widely reported in the Spanish press at the end of 1899. The writer was an object of fascination for the regional press. It was recalled that she had given a lecture in Paris on the pernicious effects of certain legends on the national mood and the possible mechanisms for revitalization. His words generated an intense controversy, a battle between the main Spanish newspapers and magazines. Months later, his speech at the opening of the Valencian Athenaeum underlined the importance of education as a means of modernization and progress. This article is interested in the representations of these events in the republican newspaper El Pueblo. It approaches the compendium of cultural, visual and textual products on the public figure of a woman of letters. Her remarkable capacity for agency and will to patriotism legitimised her dissertations on the fin-de-siècle crisis.